(untitled) (BIRDEM Medical Journal, 2025)
Background: Female urethral stricture (FUS) is a rare condition with diagnostic challenges and poor outcomes with traditional treatments. This study aimed to evaluate the effectiveness and sustainability of dorsal vaginal mucosal graft substitution urethroplasty in managing female urethral stricture. Methods: This quasi-experimental study was conducted from June 2020 to May 2023 in the Department of Urology at BIRDEM General Hospital, Enam Medical College Hospital, Dhaka Community Medical College Hospital, Evercare Hospital and Hi-Care General Hospital, Dhaka, Bangladesh. A total of 30 female patients with urethral stricture who underwent vaginal mucosal graft urethroplasty were included in the study. All participants were followed for a period of one year. Statistical analysis was performed using SPSS version 21. Results: Thirty patients underwent labial mucosal graft urethroplasty, with a mean age of 41 years and an average follow-up of 12 months. Etiologies included idiopathic (50%), iatrogenic (33.33%), traumatic (6.67%) and recurrent nonspecific urethritis (10%). The mean operative time was 90 ± 11.12 minutes, with a 100% success rate. No patient experienced severe postoperative pain, wound infection, vaginal narrowing or dyspareunia. All maintained good voiding at the 1-year follow-up. Conclusion: Dorsal vaginal mucosal graft substitution urethroplasty is an effective, sustainable and reproducible technique for treatment of female urethral stricture with minimal complications and low recurrence. BIRDEM Med J 2025; 15(3): 120-124